Do perceptions of time affect outbound-travel motivations and intention? An investigation among Chinese seniors. (April 2016) - Lu, Jiaying; Hung, Kam; Wang, Lili; Schuett, Michael A.; Hu, Liang
Abstract: How people conceptualise time can play a critical role in their travel intention. However, relatively little research attention has been directed to the links between time perspective, outbound-travel motivation and outbound-travel intention. In this study, survey data from a sample of Chinese seniors were analysed to test hypotheses regarding these links. The results showed that present-time perspective and future-time perspective were directly related to travel motivation, and that the associations between present and future perspectives and travel intention were fully mediated by travel motivation. These findings not only highlight the relevance of time-perspective styles to travel research, but also have specific implications for tourism-destination marketers with senior audiences. Highlights: This study provides the first empirical examination of seniors' travel behaviour and time perspectives. A time perspective profile for Chinese seniors is established. The associations between time perspectives and travel intention are fully mediated by travel motivations.